Healthcare-associated infections : is Portugal homogeneous? - Miranda, Sofia Farinha Vieira (2020)
Introduction: According to the ECDC, it is estimated that 3.1 million people, per year, acquire a Healthcare-Associated Infections (HAIs). In 2016-2017, Portugal had a prevalence of these infections of 9.1%, the second greatest prevalence in Europe. Despite this worrying result, there are no studies to verify the existence of intranational differences in Portuguese hospitals. Objetive: The main goal for this study is to ascertain if the prevalence of HAIs is homogeneous throughout Portuguese public hospitals, and if there were found a lack of homogeneity, this study will also identify which factors influence this variation. Methods: An analysis of the data from the ECDC administrative database was carried out regarding the Point-Prevalence Survey of HAIs in 2016/2017 in a hospital setting. This was based on the performance of the chi-square test to verify the homogeneity of the prevalence of HAIs between hospitals and, subsequently, a logistic regression model was developed that allows to identify, through proxy, which factors influence this variation and its respective weight. Findings: This study analysed 17,419 users from 82 Portuguese public hospitals, where about half of the patients analysed were male (51.4%) and that the mean age is around 61 years old. The majority of the patients had a PVC in place (65.1%), and most of the patients had a non-fatal McCabe Score (70.2%). The majority of the hospitals analysed in this study were secondary hospitals (37.8%). Conclusions: The data analysed in this study showed that there are statistically significant differences between the infection rates of the hospitals under study. The factors with the most impact in the prevalence of HAIs are the exposure to invasive procedures, whereas male patients and the number of FTE infection control nurses decrease the probability of infection.